Faktor yang Mempengaruhi Budidaya Tanaman Kopi dan Dampaknya bagi Pendapatan Petani Kopi di Desa Jenetallasa - Nur Aisyah Qadri Saiful; Nuraeni Octavia (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
This study explores the factors influencing coffee cultivation and its impact on farmers' income in Jenetallasa Village. The research applies qualitative methods through semi-structured interviews with 30 coffee farmers and 3 coffee traders. Key factors such as land area, capital, labor, and environmental conditions are analyzed. The findings reveal that these factors significantly influence coffee yield and farmer income. The study highlights the necessity of improving agricultural practices and marketing strategies to enhance farmers' economic stability.